THE EFFECT OF DIFFERENT APPLICATIONS ON FRUIT YIELD CHARACTERISTICS OF STRAWBERRIES CULTIVATED UNDER VAN ECOLOGICAL CONDITION - M. K. Gecer; E. Eyduran; H. Yilmaz (Journal of Animal and Plant Sciences, 2013)
The present study was conducted to determine the effect of different applications on fruit yield, fruit number, fruit index and soluble solid content of strawberries grown in Van ecological conditions during the years 2009-2010. In the study, low plastic tunnel and open field conditions were tested in a field experiment using Aromas, Camarosa, and Sweet Charlie strawberry cultivars. Statistical analysis of the quantitative traits such as fruit yield, fruit number, fruit index and soluble solid content was performed using two-way ANOVA (Factorial design) with three replications in order to determine the influence of the cultivar (C), application (A), and cultivar by application (CxA) interaction on these four yield traits examined. Coefficients of determination (R2%) for fruit yield, fruit number, fruit index and soluble solid content were found as 38.23 (%), 54.73 (%), 81.63(%) and 52.38 (%), respectively. Application factor significantly influenced only fruit yield (P<0.05), but it did not affect other traits. Significant effect of cultivar on fruit index (P<0.01) and soluble solid content (P<0.05) was observed. Application by cultivar interaction effect statistically influenced only fruit index (P<0.01). Low plastic tunnel gave higher value in fruit yield as compared with open field conditions in the study, but there was no significant difference in the rest of the traits with the exception of fruit yield between both applications. In fruit index, Camarosa had the highest value statistically for open field conditions compared to other cultivars, which was statistically similar to each other, but for low plastic tunnel, there were not significant differences among these three cultivars. Sweet Charlie cultivar (8.25%) producing the highest soluble solid content (SSC) amount was different from the SSC amount of Aromas cultivar, which was similar in SSC amount to Camarosa cultivar.   It was concluded in the present study that, low plastic tunnel application (475.03 g/plant) positively affected fruit yield compared to open field application (405.64 g/plant) under Van ecological condition, located in the Eastern Anatolia Region of Turkey.
Keywords: Fruit yield; Low plastic tunnel; Strawberry; Van Condition